Queer Listening: - Victoria Karlsson (Parse Journal)
This article started with a curiosity about the intersections of sound, listening and queerness, though not even queer theory at that point. I started to explore it through devising and performing an intimate one-to-one performance piece, which tried to tease out what it could mean to think about “queer” sounds and “queer” listening. As often happens in my practice, the performance became a space where I could bring various unformed and tentative ideas and topics together to work out if and/or how they related to each other. What I found, both through the performance of the piece and the subsequent analysis of its various aspects, were several interesting overlaps, similarities and intersections of sound, listening and queer theory. This text outlines the overlaps between the following areas: queer theory and sounds, queer world-building and sonic world-building, and queer listening. At this stage, I am merely sketching out these intersections and similarities. In the process of mapping out each overlap, I am finding them to be rich and full of further possible exploration and development for both creative work and research. As a starting point, I will outline what I mean when I talk about “queer theory”, and where I think I can sense an overlap with our experiences and understanding of sound and listening.